Operation of Pension Program : hearings before the United States House Committee on Veterans Affairs, Eighty-Sixth Congress, first session, on May 9, June 4, 5, 9, 10, 1959. (U.S. Congressional Hearings., 1959)
Considers H.R. 6432, to revise benefit payments for recipients of pensions for veterans with non-service-connected disabilities. Includes Presidential message "Veterans Pensions," 1959 (p. 413-463). May 9 hearing was held in Boston, Mass.